Transition towards a Green Economy in Sustainable Growth: an Analysis of Regulation and Practice in Indonesia - Naufal Abyan (Clean and Sustainability Business, 2025)
Objectives: This study aims to analyze the challenges and opportunities in implementing the green economy in Indonesia, focusing on regulatory consistency, dependence on extractive industries, and the effectiveness of government stimulus in supporting sustainable economic growth. Research Design & Methods: The research employs a qualitative approach by reviewing relevant policies, financial mechanisms, and sectoral implementations of the green economy in Indonesia. Data is collected from policy documents, industry reports, and academic literature to provide a comprehensive analysis. Findings: The findings show that Indonesia is committed to a green economy through environmentally friendly policies and practices in various sectors. The government sets targets for low-carbon development, resource efficiency, and social inclusiveness. Progress is seen in the banking sector with green credit, the furniture industry with eco-innovation, and agriculture through ISPO. Green technology and innovation play a crucial role in enhancing efficiency and promoting environmental protection. This transition represents a strategic step toward balancing economic growth, environmental sustainability, and social welfare. Implications & Recommendations: The transition to a sustainable green economy requires aligned policies, strong financial support, and effective collaboration between government, industry, and academia. Strengthened regulation, increased investment in renewable energy, and stakeholder engagement can accelerate the shift to an inclusive and resilient green economy. Contribution & Value Added: This study provides a strategic insights into Indonesia's green economy transition by highlighting key challenges and offering policy recommendations. The findings contribute to the literature on sustainable development by bridging the gap between policy implementation and sectoral economic adaptation.